A Low Cost Analysis of the Effectiveness of College of Agriculture News Releases - Laura Skillman; Haven Miller (Journal of Applied Communications, 2003)
Many colleges of agriculture have units that write news releases for distribution to local and state newspapers. Knowing where in a state these releases are most heavily used and which story topics are most likely to be printed is information that can improve the effectiveness of news release services. In this study, a clippings service was used to determine that the percentage of use was higher in certain sections of the state and with certain topics. These findings have caused a re-evaluation of the Kentucky news service and directions for further study.